Personal analysis fracture risk factors. Clinical conditions for FRAX® tool use in clinical practice - Leszczyński, Piotr; Dudziec, Ewa; Samborski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2012)
The FRAX ® tool is a computed-based algorithm which estimates 10-year probability of any major or hip fracture in an individual patient. Easy obtaining of a personal assessment and perfect interpretation of clinical fracture risk factors should determine the use of FRAX ® in the daily practice. This algorithm was developed and approved by the World Health Organization in 2008 only for primary care physicians and now it is widely used across the world. Sometimes its use may be incomprehensible and criticized by various bone specialists particularly in specific clinical situations. FRAX ® results can be underestimated or sometimes overestimated and this is the major reason for some criticism because the algorithm does not take account the exposure response e.g. glucocorticoids dose and long-term use or the number of falls. The FRAX ® model needs to be calibrated only in the countries where the epidemiology of fractures is known. This clinical application should be used in the primary assessment of the patients who are candidates for bone mineral density testing or treatment commencement. The FRAX ® algorithm should be considered by primary care physicians upon patients’ bone assessment as a reference platform but not as a gold and definitive standard. The clinical use of the FRAX ® tool requires moderate criticism in the daily practice from all clinicians who take care of patients with osteoporosis. In this paper we carefully considered not only some limitations but also strengths of the FRAX® use in clinical practice as regards best management of our patients’ bones.